Counseling a Patient with the Antenatal Diagnosis of a Cerebellar Abnormality and a Pharyngeal Cyst - Francois, Lissa; Tyagi, Rachanna; Hegyi, Thomas; Santolaya-Forgas, Joaquin (American Journal of Perinatology Reports, 2014)
Introduction Prenatal counseling with regards to the prognosis of a cerebellar abnormality is hindered not only by the diverse clinical presentations but also by the presence of subtle findings. We present a case of a distinct combination of asymmetric cerebellar hypoplasia secondary to an anterior meningoencephalocele through a clival defect that caused a severe airway obstruction in the newborn.Case Description A 21-year-old gravida 4 para 0 mother with a dichorionic–diamniotic twin pregnancy was referred for a second trimester sonographic survey. An asymmetric cerebellar hypoplasia, mega cisterna magna, and a pharyngeal cystic mass were noted on twin A. Magnetic resonance imaging report confirmed posterior fossa abnormalities and shed no light on the differential diagnosis of the cystic mass. The pregnancy ended by Cesarean delivery at 32 weeksʼ gestation after a preterm premature rupture of the membranes. Twin A had a severe airway obstruction. Postnatal evaluation confirmed a midline anterior meningoencephalocele through a defect in the clivus. The microarray chromosomal analysis demonstrated a 5q15 variant with uncertain clinical significance.Conclusion Antenatal recognition of the unique combination of a cerebellar hypoplasia with a pharyngeal cyst can impact the prenatal counseling as well as neonatal management.
Keywords: cerebellar anomaly; clivus bone; encephalocele; prenatal counseling; posterior fossa abnormality